The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1021/acsestwater.3c00017
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and Absorbance Indices for Dissolved Organic Matter from Wildfire Ash and Burned Watersheds

Sarah J. Fischer,
Timothy S. Fegel,
Paul J. Wilkerson
et al.

Abstract: Wildfires generate significant amounts of ash and burned soils that can leach altered dissolved organic matter (DOM) to watersheds. In this work, we analyzed the absorbance and fluorescence spectrum of DOM leached from 40 ash and soil samples collected from two conifer forest burn scars. DOM fluorescence quantum yield at 350 nm (ϕf350) was elevated in all ash and burned soil leachates. Wildfire DOM fluorescence was also consistently shifted toward the ultraviolet (UV) region relative to unburned materials, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…In addition, based on the small heating temperature interval, we found that the fluorescence index (FI) increased, the biological index first increased and then decreased, and the humification index (HIX) first decreased and then increased with heating temperature (Figure S3). Such results complemented a recent study that found wildfires elevated the FI and HIX values of DOM …”
Section: Resultssupporting
confidence: 88%
“…In addition, based on the small heating temperature interval, we found that the fluorescence index (FI) increased, the biological index first increased and then decreased, and the humification index (HIX) first decreased and then increased with heating temperature (Figure S3). Such results complemented a recent study that found wildfires elevated the FI and HIX values of DOM …”
Section: Resultssupporting
confidence: 88%
“…GDS-1 shows the lowest yield (1.1 g DOC kg –1 char C) followed by GDS-4 (2.1 g DOC kg –1 char C) and then GDS-30 (3.4 g DOC kg –1 char C). The low DOC yields are similar to those previously observed for laboratory-produced , and natural , chars and reflect the dominance of low solubility ConAC structures in the solid char samples.…”
Section: Resultssupporting
confidence: 84%
“…Dissolved organic carbon (DOC) and total dissolved nitrogen (TDN) were simultaneously measured on a Shimadzu TOC-L Total Organic Carbon Analyzer in precombusted amber vials within a week of leaching and filtering. Leached C and N in mg g C –1 were calculated as in eq of Fischer et al: Leachable .25em DOC .25em ( mg g C 1 ) = DOC .25em ( mg L 1 ) × leaching .25em volume .25em ( L ) / mass .25em of .25em dry .25em material .25em ( g ) × normalC .25em content .25em of .25em dry .25em material .25em ( mg C g 1 ) …”
Section: Methodsmentioning
confidence: 99%
“…Dissolved organic carbon (DOC) and total dissolved nitrogen (TDN) were simultaneously measured on a Shimadzu TOC-L Total Organic Carbon Analyzer in precombusted amber vials within a week of leaching and filtering. Leached C and N in mg g C –1 were calculated as in eq of Fischer et al: …”
Section: Methodsmentioning
confidence: 99%